YhbO Protects Cells against Multiple Stresses - Abdallah, Jad (2007)
YhbO is a member of the DJ-1/ThiJ/Pfp1 superfamily, which includes chaperones, peptidases, and the Parkinson's disease protein DJ-1. A yhbO-disrupted mutant of Escherichia coli is highly sensitive to oxidative, thermal, UV, and pH stresses, and the putative nucleophilic cysteine C104 of YhbO is required for stress resistance. These results suggest that YhbO affects a central process in stress management.